Design, synthesis, molecular docking study, and antibacterial evaluation of some new fluoroquinolone analogues bearing a quinazolinone moiety - Norouzbahari, Maryam (Daru, 2020)
BACKGROUND: Increasing bacterial resistance to quinolones is concerning. Hence, the development of novel quinolones by chemical modifications to overcome quinolone resistance is an attractive perspective in this context. OBJECTIVE: In this study, it is aimed to design and synthesize a novel series of functionalized fluoroquinolones using ciprofloxacin and sarafloxacin cores by hybridization of quinazolinone derivatives. This objective was tested by a comprehensive set of in vitro antibacterial assays in addition to SAR (structure–activity relationship) characterisation studies. METHODS: A nucleophilic reaction of ciprofloxacin and sarafloxacin with 2-(chloromethyl)quinazolin-4(3H)-one in the presence of NaHCO(3) in dimethylformamide (DMF) was performed to obtain the desired compounds 5a-j. Novel compounds were characterised by (1)H, (13)C- NMR and IR spectroscopy, MS and elemental analysis. In silico pharmacokinetics prediction assays and molecular docking studies were performed to explore the binding characteristics and interactions. Antibacterial activities of the novel compounds were evaluated by Broth microdilution, well diffusion and disc diffusion assays against three gram-positive (Methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus aureus and Enterococcus faecalis) and three gram-negative bacteria (Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli). RESULTS: The compounds exhibited moderate to good activities against gram-positive bacteria and weak to moderate activities against gram-negative bacteria. Amongst all ciprofloxacin-derivatives, compound 5d was the most potent agent with high antibacterial activity against gram-positive bacteria, including MRSA and S. aureus ((minimum inhibitory concentration (MIC) = 16 nM for both), that is 60 times more potent than ciprofloxacin as parent drug. Compound 5i from sarafloxacin-derivatives was the most potent compound against MRSA and S. aureus (MIC = 0.125 μM). Well diffusion and disk diffusion assay results demonstrated confirmatory outcomes for the quantitative broth microdilution assay. Molecular docking study results were in accordance with the results of antibacterial activity assays. CONCLUSION: The results of the current study demonstrated that the novel ciprofloxacin and sarafloxacin derivatives synthesized here have promising antibacterial activities. Particularly, compounds 5d and 5i have potential for wider antibacterial applications following further analysis. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40199-020-00373-6) contains supplementary material, which is available to authorized users.